A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak - Ng, Peter K. L.; Grinang, Jongkar (Zootaxa, 2018)
A new species of semiterrestrial highland vampire crab of the family Sesarmidae, Geosesarma larsi n. sp., is described from western Sarawak. This brings the number of Bornean Geosesarma species to 12. Geosesarma larsi n. sp. is distinguished from congeners by the structures of the carapace, third maxilliped exopod and gonopods, as well as the proportions of its ambulatory legs. The colour pattern in life is also strikingly different from allied species. Notes on its ecology are provided and conservation threats briefly discussed.